2015
DOI: 10.1063/1.4907703
|View full text |Cite
|
Sign up to set email alerts
|

Gas-dynamic acceleration of laser-ablation plumes: Hyperthermal particle energies under thermal vaporization

Abstract: The expansion of a plume produced by low-fluence laser ablation of graphite in vacuum is investigated experimentally and by direct Monte Carlo simulations in an attempt to explain hyperthermal particle energies for thermally vaporized materials. We demonstrate that the translation energy of neutral particles, ∼2 times higher than classical expectations, is due to two effects, hydrodynamic plume acceleration into the forward direction and kinetic selection of fast particles in the on-axis region. Both effects d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…In recent years there have been some reports on structuring of the laser-produced plasmas [19][20][21], with impacts in pulsed laser deposition technology. The data presented here can be correlated with the plasma structuring (into a fast structure and a slow structure, also named Coulomb and thermal structure, respectively, after the dominant ejection mechanism) during expansion based on the ablation mechanism and ionization state [21][22][23]. In recent years, a change in the understanding of this structure has been reported, and a separation based on the ionization state was more plausible for the energetic structuring of the plasma [21,[24][25][26].…”
Section: Complex System Dynamics Via Harmonic Mappingmentioning
confidence: 99%
“…In recent years there have been some reports on structuring of the laser-produced plasmas [19][20][21], with impacts in pulsed laser deposition technology. The data presented here can be correlated with the plasma structuring (into a fast structure and a slow structure, also named Coulomb and thermal structure, respectively, after the dominant ejection mechanism) during expansion based on the ablation mechanism and ionization state [21][22][23]. In recent years, a change in the understanding of this structure has been reported, and a separation based on the ionization state was more plausible for the energetic structuring of the plasma [21,[24][25][26].…”
Section: Complex System Dynamics Via Harmonic Mappingmentioning
confidence: 99%
“…Plume expansion produced by pulsed laser ablation in vacuum has been previously investigated experimentally and computationally by Direct Simulation Monte Carlo (DSMC) [7] for low-fluency regimes, when the plume ionization and plasma effects are negligible. DSMC simulations have demonstrated that hyperthermal kinetic energies, which are observed for ablated metals and graphite, can be explained through purely gas-dynamic considerations.…”
Section: Simulations Of Gas Plume Dynamicsmentioning
confidence: 99%
“…It was shown that using the calculated database of TOF distributions allows determining the irradiated surface temperature from the experimental TOF signals [ 23 ], while the commonly used fitting formulas greatly overestimate the surface temperature [ 24 ]. It was explained why the energy of particles in the TOF distribution can be several times higher than the energy of particles during evaporation and it was shown how this energy depends on the number of evaporated monolayers Θ [ 25 , 26 ]. It was shown that taking into account the time evolution of laser irradiation [ 27 , 28 ] and its spatial non-uniformity [ 29 ] has little effect on the energy and the velocity distribution function (VDF) of particles at the TOF detector.…”
Section: Introductionmentioning
confidence: 99%